51.2k views
3 votes
If cos2 x + 2cosx - 2 = 0, then cosx = _____.

A. -1 ± sqrt 3
B. 1 ± sqrt 3
C. ± sqrt 3
D. 1

2 Answers

4 votes
assuming cos2 x means cos^2 x, u can substitute y=cosx and the equation becomes: y^2 + 2y -2 =0

solving it gives the solution -1+-sqrt(3)
User Shender
by
6.0k points
2 votes

Answer:

Option D. 1

Explanation:

Thinking process:

Let the quadratic equation be given by the formula:


cos^(2) x+ 2 cosx - 2 = 0

then solving the equation using the factorization method:

using the trigonometry identity of cos 2x

then


Cos2x = 2cos^(2)x - 1

Substituting 2Cos²x - 1 gives:

2
cos^(2) x-1+cos^(2)x-2= 0

rearranging gives:


3cos^(2)x = 3\\ cosx = √(1) \\ = 1

hence cosx = 1

User Ntoonio
by
6.0k points